Kehamilan pada Usia Remaja Sebagai Faktor Risiko Terjadinya Ketuban Pecah Dini - Kevin Wahyudy Prasetyo; Affi Angelia; Novi Primadewi (Nexus Kedokteran Klinik, 2013)
Background: Premature Rupture of Membranes (PROM) is a complication that happens in 10% of pregnancy and it increases the risk of fetal death. Teenagers who get pregnant have risk for having PROM. This condition is related to nutrition factor that changes the immunity of mother. The goal of this research is to acknowledge teenage pregnancy as risk factor of PROM. Methods: This research is a case control based study. The sample used by researcher is term pregnant women with and without PROM complication with a total sample of 30 people. The data is collected from medical record and questionnaire. The data, afterwards, analyzed with multiple logistic regression analysis. Result: There is a statistically significant relationship between teenage pregnancy and PROM. Pregnant teenagers have risk to get PROM 11,808 times bigger than those of adult (p = 0,021; OR = 11,808). Conclusion: Based on the result, it can be concluded that teenage pregnancy has risk to get PROM 11,808 times bigger than those of adult. Keyword: teenage pregnancy, Premature Rupture of Membranes